Empowering Asnāf Character through Islamic Microfinance in Malaysia (Lembaga Contrarius Indonesia, 2026)
This conceptual study examines how Islamic microfinance can empower the character of asnāf entrepreneurs and thereby enhance dignified wellbeing in Malaysia. In this context, character empowerment is treated as a foundational determinant of asnāf entrepreneurs’ capacity to navigate contemporary business and life challenges. A qualitative approach is used to explore in depth the influence of Islamic microfinance on character formation, employing document analysis for data collection and content analysis for synthesis. Findings converge on three religion-anchored pillars that link financing to character development. First, spiritual cultivation strengthens tawhid and right intention so that entrepreneurship is not viewed through a purely financial lens. Second, eligibility assessment and disbursement methods are aligned with the maqāṣid, particularly hifẓ al-dīn and hifẓ al-māl, which encourage ethical conduct. Third, etiquette al-tijarah underpins work discipline, including the digitalization of business records with shariah screening to avoid gharar and tadlis. The study recommends harmonizing fatwa guidance for productive zakat instruments, instituting structured monitoring SOPs, and adopting impact indicators that include work ethics. Integrating Islamic microfinance with character empowerment is expected to strengthen the competitiveness of asnāf entrepreneurs and contribute to inclusive socioeconomic growth in Malaysia.